Climate change and sustainable urban development in Africa and Asia - Yuen, Belinda K. P.; Kumssa, Asfaw; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
This book is about African and Asian cities. Illustrated through selected case cities, the book brings together a rich collection of papers by leading scholars and practitioners in Africa and Asia to offer empirical analysis and up-to-date discussions and assessments of the urban challenges and solutions for their cities. A number of key topics concerning housing, sustainable urban development and climate change in Africa and Asia are explored along with how policy interventions and partnerships deliver specific forms of urban development. Audience: This book is intended for all who are interested in the state of the cities and urban development in Africa and Asia. Africa and Asia present, in many ways, useful lessons in dealing with the burgeoning urban population, and the problems surrounding this influx of people and climate change in the developing world.
Machine generated contents note pt. I 14. 13. 12. 11. pt. IV 10. 9. 8. 7. 6. pt. III 5. 4. 1. 3. pt. II 2. Region of Contrasts: Urban Development, Housing and Poverty in Asia Climate Change and Its Effect on Urban Housing and Liveable Cities: The Case of Harare, Zimbabwe Introduction -- Climate Change and Liveable Cities in Malaysia Climate Change and Its Effect on Cities of Eastern African Countries Africa and Asia: Two of the World's Fastest Growing Regions Climate Change and Cities' Actions in China Climate Change and Its Effect on Cities: Case Studies from Africa and Asia -- Housing and Climate Change: Adaption Strategies in Vietnam Climate Change and Urban Development -- Climate Change and Sustainable Housing in Uganda Climatic Change and Housing in Uganda Effects of Climate Change on Urban Human Settlements in Africa Climate Change in the Context of Urban Development in Africa Climate Change and Housing: Case Studies from Africa and Asia -- Climate Change and the Housing Environment in Ghana Creating a Sustainable Living Environment for Public Housing in Singapore Climate Change and Living Cities: Global Problems with Local Solutions Vinh Hung Hoang -- Kallidailkurichi Seetharam -- Michael Poku-Boansi -- Asfaw Kumssa -- Johnny Liang Heng Wong -- Zhenshan Li -- Stephen A. K. Magezi -- Ally Matano Saidi -- Aloysius Clemence Mosha -- Stephen A. K. Magezi -- Suan Siow Neo -- Kempe Ronald Hope. Sir -- Kioe Sheng Yap -- Rodreck Mupedziswa.
Electronic reproduction.
Keywords: Sustainable urban development -- Africa -- Congresses; Sustainable urban development -- Asia -- Congresses; Climatic changes -- Africa -- Congresses; Climatic changes -- Asia -- Congresses; Electronic books